Exploring Terminological Consistency of Project Management Glossaries - Papa, María Fernanda; Becker, Pablo; Olsina, Luis (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
The present paper deals with an exploratory study on the terminological consistency of four selected project management glossaries. To systematically carry out the study, eight activities were established. Regarding the information consistency sub-characteristic, this work includes a comparison and analysis of both the syntactic and semantic consistency of the terms in the glossaries. To do this, nine terminological categories were conceived for the project area, in which, for each glossary, a given term is included in a category, considering the semantics intended in the definition of the term by the authors. This categorization of terms allows us to comparatively analyze syntactic and semantic similarities, and in turn consistencies and inconsistencies. As a final goal, this study will help us examine our previously developed project ontology and recommend adoptions and adaptations.